Penerapan Sistem Informasi Dukcapil Oloh Itah (SI-DOI) Dalam Menunjang Efisiensi Tata Kelola Pemerintahan di Dinas Kependudukan dan Catatan Sipil Kota Palangka Raya - Dimas, Dimas Bagas Tita Gara; Fauzi, Erinda Alfiani; Yanur, Murniyati (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2024)
Digital-based government transformation is an obligation as well as a challenge for the government, in accordance with Presidential Decree no. 95 of 2018 concerning Electronic-Based Government Systems (SPBE) in which SPBE aims to improve efficiency and convenience so as to create efficient and quality governance. But in reality, the implementation of E-Government in digital bureaucracy has not run optimally. Therefore, this article aims to find out how the implementation of E-Government through SI-DOI services in supporting the efficiency of governance at the Disdukcapil City of Palangka Raya then looks at the quality of service and efforts to improve services. The method used is descriptive qualitative method with data collection techniques in the form of observation, interviews, documentation and the technique of determining informants in the form of purposive sampling. The results showed that the quality of service through SI-DOI was quite good because it fulfilled the 5 dimensions of quality according to Berry and Parasuraman. The application of SI-DOI as an E- Government implementation can be said to be quite successful with the existence of 3 successful elements of E-Government that are owned, thereby supporting the efficiency of the governance process. This can be seen from the benefits obtained from both parties in the form of ease of service, minimum time, cost and effort, as well as achievement according to targets for agencies by minimizing the use of resources. However, it is still not optimal enough because there are still inadequate facilities, as well as network constraints.